I need help with this question.
![I need help with this question class=](https://us-static.z-dn.net/files/dd4/822d7010a22104392833118561234111.png)
Answer:
1/6p - 4/5
Step-by-step explanation:
-2/3p + 5/6p = 1/6p because -2/3 is equal to -4/6 and 5/6 - 4/6 is 1/6
you can combine them because they both have p
1/5 - 1 = -4/5
1 = 5/5
1 - 5 = 4
1/5 - 5/5 = -4/5
you can combine the others because they both lack a variable
1/6p - 4/5
but make sure the p is not on the bottom, it's just like that because of keyboard. just put the p like it already was in the expression.